A model of sustainable urban development formation - Zavadskas, Edmundas Kazimieras; Kaklauskas, Artūras; Vainiūnas, Povilas; Šaparauskas, Jonas (International Journal of Strategic Property Management, 2010)
Life in any modern city of the world is concentrated mostly in a particular ever‐changing environment. Micro, meso and macro environments have a direct impact on sustainable urban development opportunities. This may facilitate sustainable urban development or, on the contrary, it may create constraints. Micro, meso and macro environments must be considered as an aggregate of forces influencing sustainable urban development and combining both the factors that have a direct impact and those whose impact is indirectly. This researches aim was to develop a model of sustainable urban development formation by undertaking a complex analysis of micro, meso and macro environmental factors affecting it and to present recommendations for the increase of its competitive abilities. First Published Online: 18 Oct 2010